2022
DOI: 10.56499/jppres21.1160_10.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of Piper cubeba L. extract on triple negative breast cancer MDA-MB-231

Abstract: Context: Piper cubeba L. (family Piperaceae) is used traditionally for the treatment of many diseases, including cancer. Aims: To determine the anticancer activity of P. cubeba crude extracts on cancer cells and identify chemical constituents of the active fraction. Methods: Seeds of P. cubeba were sequentially extracted with dichloromethane followed by methanol and purified using column chromatography. Fractions were screened the cytotoxicity against triple negative breast cancer (MDA-MB-468) using MTT assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…While Janeklang et al, (2014) found that tiliacorinine had an antiproliferative effect on human cholangiocarcinoma cell lines, with IC 50 values ranging from 2.59 to 7.00 µg/mL. Compared with the results of Janeklang et al, (2014), Tedasen et al, (2020) and Maungchanburi et al, (2022) extract is generally examined for in vitro cytotoxic activity if the IC 50 value in the carcinoma cells 48 -72 h after incubation is less than 20 µg/mL, and for pure compounds when the IC 50 is less than 4 µg/mL (Boik, 2001). Even though the exposure time in this experiment was 96 h, our finding might imply that E. succirubrum may have strong cytotoxic activity against CCA.…”
Section: Cell Viability Assaymentioning
confidence: 92%
See 1 more Smart Citation
“…While Janeklang et al, (2014) found that tiliacorinine had an antiproliferative effect on human cholangiocarcinoma cell lines, with IC 50 values ranging from 2.59 to 7.00 µg/mL. Compared with the results of Janeklang et al, (2014), Tedasen et al, (2020) and Maungchanburi et al, (2022) extract is generally examined for in vitro cytotoxic activity if the IC 50 value in the carcinoma cells 48 -72 h after incubation is less than 20 µg/mL, and for pure compounds when the IC 50 is less than 4 µg/mL (Boik, 2001). Even though the exposure time in this experiment was 96 h, our finding might imply that E. succirubrum may have strong cytotoxic activity against CCA.…”
Section: Cell Viability Assaymentioning
confidence: 92%
“…Piperine-free Piper nigrum L. extract, exerted a cytotoxic effect against KKU-M213 cells, with an IC 50 value of 13.70 ± 1.14 µg/ mL (Tedasen et al, 2020). Maungchanburi et al, (2022) reported that fraction DE15 from dichloromethane extract of Piper cubeba L. seed had cytotoxic activity against cholangiocarcinoma cell line KKU-M213 with an IC 50 value of 6.76 ± 0.52 µg/mL. While Janeklang et al, (2014) found that tiliacorinine had an antiproliferative effect on human cholangiocarcinoma cell lines, with IC 50 values ranging from 2.59 to 7.00 µg/mL.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…The experiment was performed in triplicate, and the absorbance's were measured at a wavelength of 750 nm (Spectrophotometer Peak Instrumental, model C-7100, USA). The total polyphenolic content was expressed in mg of gallic acid equivalent (GAE)/g of ethanolic extract (Maungchanburi et al, 2022).…”
Section: Total Polyphenol Content Using the Folin-ciocalteu Methodsmentioning
confidence: 99%
“…Copaene, another example, was detected only at the ethanol extract with 13.47% ( 18 ). Propylene glycol dominated the dichloromethane with 23.82%; however, it was not found in all other extracts ( 19 ). These differences might be attributed to the different extraction methods, detection techniques as well as geographic distribution and genetic chemotypes.…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…They include dodecanoic acid (lauric acid, 24.05%), hexadecanoic acid (palmitic acid, 11.37%), 9-octadecenoic acid (10.00%), decanoic acid (capric acid, 2.62%), 9,12-octadecadienoic acid (Z,Z) (2.50%), octadecanoic acid (2.08%), methyl decanoate (capric acid methyl ester, 1.80%), tetradecanoic acid (myristic acid, 1.66%), ethyl-(R,E)-4-hydroxy-3-methylpent-2-enoate (1.12%), along with other compounds where their concentrations did not exceed a relative abundance of 1 like palmitic acid methyl ester (0.65%) and octanoic acid (caprylic acid) (0.18%) ( 19 ). The dichloromethane fraction gave the presence of two phenolic compounds which are 4-vinylphenol and 2,4-bis(1,1-dimethylethyl)-Phenol ( 19 ). Besides, several flavonoids and phenolic acids were isolated from the aqueous extract of P. cubeba fruits such as rutin, catechin, gallic acid, caffeic acid, syringic acid, ferulic acid ( 20 , 21 ).…”
Section: Phytochemical Compositionmentioning
confidence: 99%